Sejarah masuk dan berkembangnya Islam di Indonesia: kumpulan prasaran pada seminar di Aceh - A. Hasymy (Alma'arif, 1993)
ast c.1/ir,c.2/ir,c.3/ir,c.4,ws.c.5-6/oen, c.7/ast c.8/ast c.9/oen, c.10/oen, c.11/ir,c.12-18/en, c.19